PHOSPHORYLATION OF TAU PROTEIN IN BRAIN REGIONS OF CHRONIC RENAL FAILURE - INDUCED RATS: AMELIORATIVE EFFECT OF ERYTHROPOIETIN - N, KARTHICK; Kn, Poornima; A, Saravanan; D, Alwin; P, Venkataraman (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Chronic kidney disease (CKD) is a major clinical health problem as it is a systemic disorder that causes widespread organ damage and it is related to significant morbidity and mortality. Numerous studies have shown that, cognitive dysfunction increase in prevalence, due to increase in reactive oxygen species in CKD severity. Tau proteins are proteins that stabilize microtubules. Hyperphosphorylation of tau reduces its ability to bind to microtubule causes dystabilization and production of neurofibrillary tangles (NFT) and neurodegeneration in the brain. Aberrant hyperphosphorylation of tau is critical to the progression of neurodegeneration. Erythropoietin (EPO), a glycoprotein has been in clinical use for millions of anemic patients, and some studies show it has a neuroprotective role. Till now studies on the level of tau protein phosphorylation in brain regions of CKD-induced experimental animals and impact of EPO therapy are scarce. The aim of this study is to determine the impact of CKD and EPO therapy on tau protein phosphorylation in brain regions of experimental rats. Methods: This study was performed on 48 adult male Wistar rats. Two phases were conducted to find out the difference between simultaneous and posttreatment of EPO. Phase I: 24 adult male Wistar rats were divided into 4 groups (6 animals each): Group 1: Control, Group 2: 0.75% of adenine mixed diet for 4 weeks, Group 3: 0.75% of adenine mixed diet was given for 4 weeks and simultaneous administration of EPO (100 IU/kg btw, ip) thrice weekly. Group 4: EPO alone (100 IU/Kg btw, ip) thrice per week. All the animals were sacrificed uniformly at the end of 4 weeks. In Phase II, 24 animals were maintained separately for 40 days experimental period and divided into 4 groups. Groups 1, 2, and 4 animals were treated as same mentioned in Phase I. Group 3: For EPO posttreatment, adenine mixed diet was given for 4 weeks for chronic renal failure (CRF) induction. After the 4 week, EPO (100 IU/Kg btw.) was administered daily once for 12 days. At the end of the 40 days, all the animals were sacrificed uniformly. In both the phases after the treatment period, the brain tissue was removed and samples were homogenized. Total tau protein and phosphorylated tau protein expressions were analyzed by western blotting method. Results: In results, both the total tau and phosphorylated tau protein levels were significantly increased all the brain regions of CRF-induced groups when compared to control. In both simultaneous and posttreatment of EPO, the levels were retrieved. Conclusion: This study proves that EPO supplementation has a promising role in neuroprotection by preventing abnormal phosphorylated tau protein accumulation. This study also proves the clinical usefulness of EPO as a supplemental therapeutic agent in neurotoxicity. Keywords: Chronic renal failure, Cognitive dysfunction, Hyperphosphorylation of tau protein, Erythropoietin. th